2022
DOI: 10.24042/ijecs.v2i2.14815
|View full text |Cite
|
Sign up to set email alerts
|

Deep Transfer Learning Networks for Brain Tumor Detection: The Effect of MRI Patient Image Augmentation Methods

Abstract: The exponential growth of deep learning networks has enabled us to handle difficult tasks, even in the complex field of medicine with small datasets. In the sphere of treatment, they are particularly significant. To identify brain tumors, this research examines how three deep learning networks are affected by conventional data augmentation methods, including MobileNetV2, VGG19, and DenseNet201. The findings showed that before and after utilizing approaches, picture augmentation schemes significantly affected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…With the help of their investigation, the researchers were successful in obtaining a 92.34 percent F1 detection score with the ResNet50 network. Abdalla et al [18] investigated typical data augmentation methods' effects on three deep learning networks, namely MobileNetV2, VGG19, and DenseNet201, to detect brain tumors. The results demonstrated that picture augmentation schemes had a significant impact on the networks both before and after using approaches.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the help of their investigation, the researchers were successful in obtaining a 92.34 percent F1 detection score with the ResNet50 network. Abdalla et al [18] investigated typical data augmentation methods' effects on three deep learning networks, namely MobileNetV2, VGG19, and DenseNet201, to detect brain tumors. The results demonstrated that picture augmentation schemes had a significant impact on the networks both before and after using approaches.…”
Section: Literature Reviewmentioning
confidence: 99%